2018
DOI: 10.1029/2017gc007417
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity, Metamorphism, and Fluid Evolution Across the Northern Cascadia Fore Arc

Abstract: We invert traveltime data from regular seismicity and low‐frequency earthquakes (LFEs) on southern Vancouver Island to map fore‐arc structure and seismogenesis. Tomographic images reveal high Poisson's ratios associated with a previously mapped, dipping low‐velocity zone inferred to be overpressured, upper oceanic crust of the Juan de Fuca plate, where LFEs and other slow‐slip phenomena occur. Low Poisson's ratios (∼0.225) in the fore‐arc continental crust above the mantle wedge are accompanied by high Vp (∼6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 86 publications
8
58
0
Order By: Relevance
“…At ETS depths (30 to 40 km), most fluids derive from prograde metamorphic dehydration reactions of subducting material (8). Studies of subduction zone forearcs suggest that fluids eventually migrate along the megathrust and into the overlying crust, near the mantle wedge corner (14)(15)(16). It has been suggested that these fluids may not only play a passive role in ETS by weakening faults via high P f but that ETS may also be coupled with cyclic fluid processes (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At ETS depths (30 to 40 km), most fluids derive from prograde metamorphic dehydration reactions of subducting material (8). Studies of subduction zone forearcs suggest that fluids eventually migrate along the megathrust and into the overlying crust, near the mantle wedge corner (14)(15)(16). It has been suggested that these fluids may not only play a passive role in ETS by weakening faults via high P f but that ETS may also be coupled with cyclic fluid processes (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of subduction zone forearcs suggest that fluids eventually migrate along the megathrust and into the overlying crust, near the mantle wedge corner (14)(15)(16). It has been suggested that these fluids may not only play a passive role in ETS by weakening faults via high P f but that ETS may also be coupled with cyclic fluid processes (14)(15)(16)(17)(18). However, observations of these cyclic processes are limited and indirect (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study in Kanto, Japan found that seis-micity rates and seismic attenuation above the plate interface changed following slow slip, suggesting slow slip releases trapped fluids that then migrate updip along the plate interface until they migrate into the overlying crust via an inherent permeable zone where they can trigger seismicity (79). Furthermore, in northern Cascadia, Savard et al (80) attribute vertically clustered, swarmlike seismicity that is concentrated in the forearc continental crust above the mantle wedge downdip of the tremor zone to trapped fluids released from the plate interface, while Wells et al (81) fluids released from the subducting crust. If the megathrust is well-drained, then the overpressurized fluids that flow along crustal faults would facilitate shallow seismicity due to the consequent increase in pore-fluid pressures and decrease in the shear strength of the crustal faults (49,83,84), which would explain the occurrence of our swarm seismicity and a-SSEs along the sliver fault.…”
Section: Discussionmentioning
confidence: 89%
“…The porosity is shown near the cross symbols. (b) V p and V p / V s observed in the fore‐arc mantle wedge in the southern Western Alps (Solarino et al, ) and Cascadia subduction zones (Ramachandran & Hyndman, ; Savard et al, ) along with those of the serpentinized harzburgite.…”
Section: Resultsmentioning
confidence: 99%
“…In Cascadia, the temperature of the fore‐arc mantle wedge is estimated to be mostly higher than 450 °C due to the subduction of young and hot oceanic lithosphere (Wada & Wang, ) and thus preferential Opx reaction is possible as in the southern Western Alps subduction zone. However, seismic observations revealed the presence of low V p and high V p / V s anomalies in the Cascadia fore‐arc mantle ( V p = 7.2–7.6 and V p / V s = 1.76–1.81, Ramachandran & Hyndman, ; Savard et al, ), which cannot be explained by the presence of talc (Figure b). This anomaly is rather consistent with the stoichiometric serpentinization which produces only serpentine as a hydrous mineral.…”
Section: Discussionmentioning
confidence: 96%